Risk Factors for Diabetic Peripheral Neuropathy, Peripheral Artery Disease, and Foot Deformity Among the Population With Diabetes in Beijing, China: A Multicenter, Cross-Sectional Study - Liu, Jiayi; Yuan, Xiaoyong; Liu, Jin; Yuan, Geheng; Sun, Yalan; Zhang, Donghui; Qi, Xin; Li, Huijuan; Zhang, Junqing; Wen, Bing; Guo, Xiaohui (Frontiers in Endocrinology, 2022)
Diabetic peripheral neuropathy (DPN), peripheral artery disease (PAD), and foot deformity are the most common causes of diabetic foot, which can considerably worsen the patient’s quality of life. In this study, we aimed to investigate the prevalence and risk factors associated with DPN, PAD, and foot deformity among patients with diabetes living in Beijing, China. In total, 3,898 diabetes patients from 11 hospitals in Beijing were evaluated using questionnaires and physical examinations, and 3,758 patients were included in the analysis. We compared the demographic, clinical, biological characteristics, and comorbidities of patients with and without DPN, PAD, or foot deformity, and used binary logistic regression analysis to identify potential factors associated with these outcomes. Overall, 882 patients (23.5%) had DPN, 437 patients (11.6%) had PAD, and 1,117 patients (29.7%) had foot deformities, including callus. The risk factors for DPN included: age ≥40 years, a ≥10+year duration of diabetes, a body mass index of <18.5 kg/m2 or ≥24 kg/m2, a systolic blood pressure (SBP) of ≥140 mm Hg, a hemoglobin A1c (HbA1c) level of ≥7%, chronic kidney disease, and cerebrovascular disease. The risk factors for PAD included: a 15+ year diabetes duration, a body mass index of <18.5 kg/m2, a systolic blood pressure (SBP) of ≥140 mm Hg, a HbA1c level of ≥7%, chronic kidney disease, coronary heart disease, and cerebrovascular disease. The risk factors for skeletal foot deformities included: women, age ≥40 years, a SBP ≥140 mm Hg, and hyperlipidemia. The risk factors for callus formation included: women, a SBP ≥140 mm Hg, and hyperlipidemia. In conclusion, the prevalence of foot deformities was higher than DPN and PAD in patients with diabetes. Managing the risk factors for DPN, PAD, and foot deformity is important for reducing the risk of diabetic foot.